Effect of substrate angle on the growth of MoS2 vertical nanosheets using a one-step chemical vapor deposition. (13th July 2018) - Inguva, Saikumar; Cai, Jian-Hui; Hu, Cong; Wu, Jing; Lu, Youming; Liu, Xinke
Abstract: The production of the vertically aligned MoS2 nanosheets has been generating an enormous interest due to their potential applications in the diverse research fields. However, the production methods for such vertical nanosheets, especially via chemical vapor deposition (CVD) route, used so far have involved complex- or multi-growth processing steps. To meet this demanding challenge, in this work we report high quality vertically aligned MoS2 nanosheets grown by CVD in a single growth step, with reduced complexity of the growth processing steps. For the first time, we also studied the effect of substrate angle (ranging from 0° to 90°) during the growth on surface morphology, structural, and Raman spectroscopy properties of the as-grown MoS2 vertical nanosheets. The results demonstrated that high quality vertically aligned nanosheets with packed density can possibly be achieved at 90° substrate angle. The characterizations such as XRD, HR-TEM and SAED patterns confirm the vertical orientation while SEM images reveal the excellent surface morphology and packed density of the MoS2 vertical nanosheets. Additionally, Raman spectroscopy studies further evident of the verticality nature of the high quality nanosheets while XPS data confirmed that the as-grown material is of MoS2 . The relevance of the work is discussed in the context of the present fabrication methods for such vertically aligned MoS2 nanosheets and also suggested their domains of applications.